Land Cover Dynamics and Implications on Water Resources in Bamenda III Sub-Division, North West Region, Cameroon - Ndikebeng, Kometa Raoul; Forba, Cletus Fru; Paul Tume, Suiven John; Yenlajai, Banseka JaneFrances; Kimengsi, Jude Ndzifon (International Journal of Global Sustainability, 2023)
There exists a complex relationship between land use change and hydrology as exemplified by the quantification of its spatio-temporal impacts. Water resources are stressed by significant land use alterations linked to rapid population growth and urbanization in Bamenda III. This paper analyzes the trend of land use activities in Bamenda III Sub-Division, using LANDSAT images of 1986, 2003 and 2022, to portray land use dynamism over space, their impacts on water resources, and the planning implications thereof. To achieve this, a random survey of 70 households in Bamenda III was conducted, complemented by key informant interviews. The results indicate that significant changes have been recorded in land uses brought about by population growth and urbanization. Seventy percent (70%) of water resources including wetlands and water catchments have been lost to infrastructural development and agriculture. The expansion, and replacement of land uses has stressed water resources, resulting in watershed degradation, deforestation and floods. Water sources like streams and rivers have witnessed a decline in their flow characteristics. The study recommends the strict implementation of town planning laws, to assure the sustainability of water resources.